2023
DOI: 10.3126/ije.v12i1.52442
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Burning and its Effects on Shorea robusta (Sal) Regeneration in Dhansar Block Forest, Rautahat

Abstract: Fire is used as a management tool to administer a wide range of ecosystems worldwide. Forest fires in Shorea robusta (Sal-dominated) forests take the form of ground fires and mostly affect regeneration. We investigated the effect of forest fire on Sal regeneration in 42 sample plots, of which 21 were subjected to controlled burning. The results showed that species richness decreased from fire-unaffected (19) to fire-affected (10). The total density of Sal seedlings in the fire-affected sites was 3829 seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Te fnding may be attributed to the loss of nutrients by volatilization due to the lower volatilization temperature (774 °C) of potassium. Dhungana et al [80] concluded that low-intensity wildfres can serve as a valuable means of regenerating seedlings of S. robusta. Tus, the positive efect may be attributed to the enhanced physicochemical properties of the soil following the post-fre efect.…”
Section: Comparisons Of Soil Parameters Betweenmentioning
confidence: 99%
“…Te fnding may be attributed to the loss of nutrients by volatilization due to the lower volatilization temperature (774 °C) of potassium. Dhungana et al [80] concluded that low-intensity wildfres can serve as a valuable means of regenerating seedlings of S. robusta. Tus, the positive efect may be attributed to the enhanced physicochemical properties of the soil following the post-fre efect.…”
Section: Comparisons Of Soil Parameters Betweenmentioning
confidence: 99%